(untitled) (Research, Society and Development, 2023)
Cheese is a fresh or cured dairy product, composed of proteins, lipids, minerals, carbohydrates, vitamins, calcium and phosphorus, produced by the coagulation of milk. The present work aimed to evaluate the influence of sound waves and the influence of the magnetic field on the development of fungi that grow on cheese. Three experiments were performed using sound waves at different exposure intervals (6h/day for 7 days, 6h/day for 11 days and 24h/day for 7 days) and 2 experiments using the magnetic field (3 days and 7 days). In experiments with ultrasonic waves, it was observed that the change in the odor of cheeses that were subjected to ultrasound occurred before those that were not subjected to ultrasound, but the other changes were not significant. In the experiments under the influence of the magnetic field, significant sensory changes were observed in both cycles in relation to the control sample in terms of the appearance of visually detectable fungal colonies.